2020
DOI: 10.1093/ajcn/nqaa220
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation is an illusion, only present when participants are in negative energy balance

Abstract: Background The existence of metabolic adaptation, following weight loss, remains a controversial issue. To our knowledge, no study has evaluated the role of energy balance (EB) in modulating metabolic adaptation. Objectives The aim of this study was to determine if metabolic adaptation, at the level of resting metabolic rate (RMR), is modulated by participants’ EB status. A secondary aim was to investigate if metabolic adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 40 publications
6
53
0
Order By: Relevance
“…A recent study by Heinitz et al (79) reported the presence of adaptive thermogenesis during Phase 2 at weeks 1 and 3 with weight loss of about 100 kcal/d, the same average magnitude as observed by Muller et al (74). Martins et al (67) also observed an adaptive thermogenesis level of 90 ± 94.5 kcal/d ( P < 0.001) after 8 weeks of a 1,000 kcal/d low‐energy diet in participants with obesity. Adaptive thermogenesis was no longer significant (26.8 ± 121.5 kcal/d) following 4 weeks of weight stabilization during which the participants gained a small amount of weight.…”
Section: Weight Loss Effectsmentioning
confidence: 88%
See 3 more Smart Citations
“…A recent study by Heinitz et al (79) reported the presence of adaptive thermogenesis during Phase 2 at weeks 1 and 3 with weight loss of about 100 kcal/d, the same average magnitude as observed by Muller et al (74). Martins et al (67) also observed an adaptive thermogenesis level of 90 ± 94.5 kcal/d ( P < 0.001) after 8 weeks of a 1,000 kcal/d low‐energy diet in participants with obesity. Adaptive thermogenesis was no longer significant (26.8 ± 121.5 kcal/d) following 4 weeks of weight stabilization during which the participants gained a small amount of weight.…”
Section: Weight Loss Effectsmentioning
confidence: 88%
“…This approach has the same effect as modifying the Harris‐Benedict equations by replacing Wt with adipose tissue and ATFM or fat mass and FFM. There are many published versions of these statistical REE prediction models that also include age, sex, and other covariates (67,68).…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in those with weight gain between week 9 and week 13, no metabolic adaptation was seen at week 13. Metabolic adaptation after WL was also not correlated with weight regain at the 1-year follow-up ( r = 0.034; P = 0.824; n = 45) ( 46 ). These 2 studies clearly show that metabolic adaptation at the level of RMR is minimal when measurements are taken under conditions of weight stability, and most likely not present under conditions of EB, and does not predict weight regain long term.…”
Section: Compensatory Responses To Weight Lossmentioning
confidence: 99%